Design of frameworks for self‐adaptive service‐oriented applications: A systematic analysis. (30th June 2021) - Filisbino Passini, William; Aparecida Lana, Cristiane; Pfeifer, Vinicius; Affonso, Frank José
Abstract: Self‐adaptive service‐oriented Applications (Self‐Apps) must be able to understand themselves or the environment in which they are executed, and propose solutions to meet changing conditions. The development of these applications is not a trivial task, since it encompasses issues from different research areas. Despite the importance of frameworks for Self‐Apps, there is a lack of comprehensive analysis of how the design of such applications is performed, and regarding the standardization of concepts and coverage of minimum requirements for Self‐Apps. The main contribution of this article is to present this comprehensive analysis, providing the state of the art for this subject. This analysis was built through a Systematic Mapping Study, based on a total of 65 studies, from which we identify the main attributes for Quality of Service (QoS), search strategies, and service management strategies employed in the design of frameworks for Self‐Apps. The main aspects of requirements involved in the design of Self‐Apps were pointed out to stakeholders. For example, these applications must implement a method for evaluation of QoS based on metrics. We also put forward the S‐Frame, a modular solution that brings together the main features for the design of Self‐Apps, and describe the main challenges concerning these applications.